VO#46 Quotation for RCC equipment foundation at B2, B1 & GF rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of quotation for RCC equipment foundation at Basement 1-2 and ground floor of BRACU new campus building.